Association between sleep quality and screen time in adolescents (Research, Society and Development, 2021)
In The aim of the present study was to evaluate the association between sleep quality and screen time among adolescent students. A cross-sectional study was conducted with adolescents between 15 and 19 years of age at a public high school in the city of Recife, Brazil. Data were collected through digital questionnaires using the Google Forms tool: questionnaire addressing sociodemographic characteristics, Pittsburgh Sleep Quality Index (PSQI) and Electronic Media Questionnaire. Statistical analysis involved either Pearson's chi-square test or Fisher's Exact test, with a 95% confidence interval and 5% significance level. The sample consisted of 128 adolescents (mean age: 16.20 years; 62.5% female). Most participants (65.6%) slept eight or more hours per night and 62.5% considered their sleep quality to be good. Cellular phone use time ≥4 hours/day was associated with poor sleep quality. Associations were also found between poor sleep quality and use after 10 pm of computers [OR (95% CI): 10.6 (2.6 to 42.0); p (1)